Analisis Tegangan Roda Gigi Miring pada Transmisi Kendaraan Roda Empat berdasarkan AGMA dan ANSYS - Sutanto, Hadi (Media Teknika, 2017)
Two kinds of stresses in the gear teeth are root bending stress and tooth contact stress. These two stresses results in the failure of gear  teeth.  The root bending stress results in fatigue failure and contact stress results in pitting failure at the contact surface. The stress analysis used to minimize gear  failure in the  design of helical gear.  It is also optimize the  design of helical gear  on the transmission system of the truck motor vehicle, where the power transmission is required at heavy loads  with  smoother  and  noiseless operation.  In this  paper  bending  stress  and  contact  stress estimated  using analytical method while modeling of gears used the numerical solution. Method of beam strength  based on modified Lewis calculation used to predict the bending strength  of helical gears. Contact stress was estimated  using related method of AGMA contact stress. Stress modeling of helical gears is done by ANSYS 14.5, which is a finite element analysis package. The results are then compared with both AGMA and ANSYS procedures. The values of bending strength and contact stress determined using AGMA method found to be compatible with ANSYS simulation.